Asymmetric Si-rhodamine scaffolds: rational design of pH-durable protease-activated NIR probes in vivo. Issue 16 (30th January 2020) - Li, Min; Wang, Chuanfeng; Wang, Ting; Fan, Mengting; Wang, Ning; Ma, Danying; Hu, Ting; Cui, Xiaoyan
Abstract : A group of asymmetric Si-rhodamine scaffolds was designed for protease-activated NIR probes. Abstract : A group of asymmetric Si-rhodamine scaffolds was designed for protease-activated NIR probes. Dual pH-inertia for both spirocyclized fluorescent probes and fluorescent products of zwitterions form over a wide range of pH (4.0–11.0). Leucine aminopeptidase (LAP) and γ-glutamyl transpeptidase (GGT) were monitored by fluorescent imaging in vivo .